Life expectancy and early to mid-term dysfunction of transcatheter aortic prostheses: incidence, modes, correlates, and outcome. (3rd October 2022) - Nitsche, C; Koschutnik, M; Dona, C; Mutschlechner, D; Spinka, G; Dannenberg, V; Mascherbauer, K; Sinnhuber, L; Kammerlander, A; Winter, M P; Bartko, P E; Goliasch, G; et al.
Abstract: Backgrounds: Bioprosthetic valve dysfunction (BVD) is a major concern regarding transcatheter aortic valve implantation (TAVI) in low-risk patients. Aims: To assess incidence, determinants, modes, and outcome of early to mid-term BVD after TAVI in relation with life expectancy. Methods: Consecutive TAVI recipients (2007–2020) with a post-interventional follow-up ≥1-year were prospectively included. BVD components and bioprosthetic valve failure (BVF) were assessed according to updated Valve-Academic-Research-Consortium-3 criteria. Echocardiographic and laboratory follow-up was performed prior to discharge, at 3- and 12-months, and yearly thereafter. BVD/BVF and all-cause death served as endpoints. Average life expectancy was calculated from National Open Health Data and patients were stratified according to tertiles (1st: <6.85y, 2nd: 6.85–9.7y, 3rd: >9.7y). Results: Of 1047 patients (81.6±6.8 y/o, 52.7% female, EuroSCORE II 4.5±2.5), ≥2 follow-ups were available from 622 (serial echo cohort). After a median echo follow-up of 12.2 months, incidence rates of BVD and BVF were 8.4% [95% confidence interval 6.7–10.3], and 3.5% [2.5–4.9] per valve-year, respectively, without differences between life expectancy tertiles (Figure 1). BVD incidence was double within the first year of implant (9.9% [7.7–12.6] per valve-year; mostly non-structural VD) vs. beyond (4.8% [3.1–7.2] per valve-year; structural and non-structural VD). Valve-in-valve procedure, and stenosis severity (both p<0.05), but not age/life expectancy (p>0.5) predisposed for BVD. After 4.4±3.0 years, mortality was 36.7%. Time-dependent BVD/BVF were independently associated with outcome for patients in the first (adjusted hazard ratio [AHR] 1.72 [1.06–2.88]/ 2.97 [1.72–6.22]) and second (AHR 1.96 [1.02–3.73]/ 2.31 [1.00–5.30]), but not the third tertile of life expectancy (AHR 1.42 [0.66–3.12]/ 1.84 [0.71–4.79]; Figure 1). Conclusions: In this large prospective observational cohort, early to mid-term BVD after TAVI occurred at the same rate across the spectrum of life expectancy and was not prognostic among those with the longest life expectancy. Funding Acknowledgement: Type of funding sources: None.